Regional Autonomy and Tax Law: An Analysis of Local Tax Effectiveness in Promoting Regional Development - Nurochman, Rafli; Rahmawati Suci Ranifah,; Chinta Chintia Nuraisyah, (Candidate: Jurnal Sains Politik, 2024)
In the context of Indonesia’s decentralization era, regional autonomy was introduced to empower local governments in managing their own resources and finances. However, despite increased authority, many regions remain heavily dependent on central government transfers, and the contribution of local taxes to regional development is often suboptimal. This scientific research focuses on the effectiveness of tax law policies and regional autonomy in improving regional development. The aim is to understand the definitions of regional autonomy and tax law, followed by an analysis of why the role of regional taxes has not been optimal in financing local development, and how these taxes can be leveraged to better support for development objectives. In this research, the author uses a qualitative method with a descriptive-analytical approach to strengthen data validation. The final results of the research, based on a review of several books and scientific journals, show that regional development problems remain an ongoing challenge for the government in managing public tax revenues. The study emphasizes the importance of strengthening bureaucratic integrity and transparency in tax management; increasing public outreach regarding tax compliance and the use of tax funds; and promoting a regional autonomy system that is adaptive to local culture, customs, and geography. These approach is considered suitable and effective in promoting regional development programs.